Effects of Seed-Applied Biofertilizers on Rhizosphere Biodiversity and Growth of Common Wheat (Triticum aestivum L.) in the Field - Dal Cortivo, Cristian; Ferrari, Manuel; Visioli, Giovanna; Lauro, Marta; Fornasier, Flavio; Barion, Giuseppe; Panozzo, Anna; Vamerali, Teofilo (Frontiers in Plant Science, 2020)
In order to reduce chemical fertilization and improve the sustainability of common wheat (Triticum aestivum L.) cultivation, maintaining at the same time high production and quality standards, this study investigated the effects of three commercial biofertilizers on rhizosphere bacterial biomass, biodiversity and enzymatic activity, and on plant growth and grain yield in a field trial. The wheat seeds were inoculated with the following aiding microrganisms: (i) a bacterial consortium (Azospirillum spp. + Azoarcus spp. + Azorhizobium spp.); and two mycorrhizal fungal-bacterial consortia, viz. (ii) Rhizophagus irregularis + Azotobacter vinelandii, and (iii) R. irregularis + Bacillus megaterium + Frateuria aurantia, and comparisons were made with non-inoculated controls. We demonstrate that all the biofertilizers significantly enhanced plant growth and nitrogen accumulation during stem elongation and heading, but this was translated into only small grain yield gains (+1-4% vs controls). The total gluten content of the flour was not affected, but in general biofertilization significantly upregulated two high-quality protein subunits, i.e., the 81 kDa high-molecular-weight glutenin subunit and the 43.6 kDa low-molecular-weight glutenin subunit. These effects were associated with increases in the rhizosphere microbial biomass and the activity of enzymes such as beta-glucosidase, -mannosidase, -mannosidase and xylosidase, which are involved in organic matter decomposition, particularly when Rhizophagus irregularis was included as inoculant. No changes in microbial biodiversity were observed. Our results suggest that seed-applied biofertilizers may be effectively exploited in sustainable wheat cultivation without altering the biodiversity of the resident microbiome, but attention should be paid to the composition of the microbial consortia in order to maximize their benefits in crop cultivation.